INTEGRATING ISLAMIC EDUCATION TO DEVELOP CHARACTER IN SPECIAL NEEDS STUDENTS AT SMP MUHAMMADIYAH 18 SURABAYA - Surya Alam Semesta Wisran Abdul Malik; Muhammad Arfan Mu’ammar; Hayumuti Hayumuti (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2025)
This study examined how implementing Islamic Religious Education instruction shapes the character of students with special needs attending inclusive schools, such as SMP Muhammadiyah 18 Surabaya. Islamic Religious Education is the primary resource for character education in Islamic schools like SMP Muhammadiyah 18 Surabaya. However, this effort faces serious challenges when faced with specific student conditions, including students with special needs. As an inclusive school, the school needs to implement special strategies to ensure the learning process runs as expected. Therefore, this study attempted to analyse these strategies. This qualitative study used data collection techniques such as interviews, observation, and documentation. This study revealed several strategies and approaches to Islamic Religious Education (IRE) teaching for students with special needs, including shadow-teacher mentoring, role-model-based learning, and special classes. These strategies were deemed quite effective, successfully changing the behaviour of children with special needs in their daily lives, particularly in carrying out religious obligations. However, further development of learning methods and teacher training was necessary to develop inclusive teaching strategies tailored to students' special needs.